Electrophysiological studies of the production and cortical representation of vocalisations in the guinea pig - Green, David Brian (2014)
Vocal production: Guinea pigs (GP) are gregarious animals with a well-characterised repertoire of 11 vocalisations. These are context dependent, communicating information about danger, identity and emotional state. Vocalisations have previously been produced by electrical stimulation of three areas in the GP brain: anterior cingulate, hypothalamus and periaqueductal grey. These vocalisations were reported as natural-sounding, but with little or no spectral analysis to support this assertion. I elicited calls from urethane-anaesthetised GP by stimulating all the above areas, and from the amygdala and several thalamic nuclei. The spectrotemporal properties of these vocalisations were analysed and eight distinct vocal patterns were identified. For comparison, recordings of spontaneous calls from the same colony (Grimsley et al., 2012) were analysed in the same way, then used to name the electrically elicited calls. For six call types the matches between electrically elicited and spontaneous calls were unambiguous. The remaining two elicited calls were identified as being slightly unnatural versions of one spontaneous call. Five calls were produced during the (1.6 s) electrical stimulation and three were produced after the stimulation, lasting up to 30 s. Concurrent bilateral stimulation of loci producing post-stimulus calls always had an additive effect, whereas stimulation of two loci giving during-stimulus calls was more complex. Auditory representation of vocalisations: To date, eight functional areas of GP auditory cortex have been identified using electrophysiology, and their responses to vocalisations has been investigated previously. I have discovered a new area, ventral to those currently described, which was named deep ventrorostral belt (dVRB). It is unresponsive to a broad range of puretone auditory stimuli, yet is highly selective to conspecific vocalisations. Single neuron recordings were taken from dVRB and the primary auditory region (AI) during the audio-vocal study. Audio-vocal interactions: The vocal production system communicates the expected sensory consequences of its action. This allows the auditory system to discriminate between self-produced and external sounds. These sensorimotor connections originate in premotor areas of the midbrain as well as motor planning areas of neo- and paleocortex. The basal amygdala (BA) – an emotion-mediating structure – yields vocalisations in GP when stimulated, and is involved in the affective prosody of human speech. It was hypothesised, therefore, that BA would also have an audio-vocal role. A protocol was developed to combine electrical stimulation in BA with auditory presentation of a range of GP vocalisations, whilst recording neural activity in AI and dVRB. In both cortical areas, single-neuron responses demonstrated a complex interaction of electrical and auditory stimuli; showing both enhanced or suppressed responses, depending on call type.